Paper-Based Biosensors for Management of Emerging Infectious Disease: A Brief Review - Mungmunpuntipantip, Rujittika; Wiwanitkit, Viroj (Journal of Sustainable Materials Processing and Management, 2022)
The current worldwide challenge is emerging infectious illness. The pandemic's billions of infected cases necessitate an emergency response to contain the outbreak. An early diagnosis and rapid treatmentis a crucial idea for managing the outbreak. In order to diagnose growing infectious diseases, new biosensors are being developed as new therapies that are hoped to aid in accurate diagnosis. The materials for development of new tools for using as new infectious disease detection biosensors are extremely interesting topic in clinical material science. Good sustainable material is accepted for development of the new biosensor. The authors summarize and analyze sustainable materials and emerging infectious disease detection biosensors in this brief study, witha particular focus on COVID-19 and Zika virus infection. In this review, the paper-based biosensor for the "management of emerging infectious disease is summarized and discussed. Specific examples on COVID-19 and Zika virus disease are provided in this article.